Dimensionality reduction bistatic radar clutter suppression technique based on three-dimensional cross-beam - CHENG, Yufeng; LI, Yong; CHEN, Fengfeng; DENG, Xiaobo; CHENG, Wei (Xibei Gongye Daxue Xuebao, 2023)
Aiming at the problem that the non-stationary of airborne bistatic radar clutter reduces the performance of traditional clutter suppression algorithm, this paper first formulates airborne bistatic radar clutter model, and then analyzes the bistatic radar clutter characteristics in four typical combat scenarios. In addition, in order to reduce the computation burden of the STAP algorithm, a three-dimensional cross-beam clutter suppression algorithm is proposed, which uses the transformation matrix to convert the space-time two-dimensional data into azimuth-elevation-Doppler three-dimensional data. By eliminating auxiliary beam clutter data, only the main beam clutter data which plays a major role in dual-basis clutter suppression is retained to form a three-dimensional cross-beam for local adaptive clutter suppression. The proposed algorithm can greatly reduce the amount of calculation and the demand of training samples, while trying to ensure that the clutter suppression performance does not degrade. The effectiveness of the proposed algorithm is verified by analyzing the clutter suppression effect and computation amount of various algorithms in typical combat scenarios. Therefore, the algorithm has great potential in the applications of airborne bistatic and non-stationary clutter suppression. 针对机载双基雷达杂波非平稳性导致传统杂波抑制算法性能下降的问题, 对机载双基杂波进行建模, 在此基础上, 分析了4种典型作战场景下的双基杂波特性。为降低STAP算法的计算量, 提出一种三维交叉波束杂波抑制算法。该算法采用变换矩阵将空时二维数据转换为方位-俯仰-多普勒三维数据, 剔除辅助波束杂波数据, 只保留对双基杂波抑制起主要作用的主波束杂波数据, 形成三维交叉波束进行局部自适应杂波抑制, 在大幅降低算法计算量与训练样本需求量的同时尽量保证杂波抑制性能不下降。通过分析多种算法在典型作战场景下的杂波抑制效果与计算量, 验证了所提算法有效性。所提算法在机载双基以及非平稳杂波抑制方面的应用潜力巨大。